The Language of Vision*. (March 2021) - Cavanagh, Patrick
The descriptions of surfaces, objects, and events computed by visual processes are not solely for consumption in the visual system but are meant to be passed on to other brain centers. Clearly, the description of the visual scene cannot be sent in its entirety, like a picture or movie, to other centers, as that would require that each of them have their own visual system to decode the description. Some very compressed, annotated, or labeled version must be constructed that can be passed on in a format that other centers—memory, language, planning—can understand. If this is a "visual language, " what is its grammar? In a first pass, we see, among other things, differences in processing of visual "nouns, " visual "verbs, " and visual "prepositions." Then we look at recursion and errors of visual grammar. Finally, the possibility of a visual language also raises the question of the acquisition of its grammar from the visual environment and the chance that this acquisition process was borrowed and adapted for spoken language.